2017
DOI: 10.1177/1550059417715388
|View full text |Cite
|
Sign up to set email alerts
|

Comparing EEG Nonlinearity in Deficit and Nondeficit Schizophrenia Patients: Preliminary Data

Abstract: Electroencephalogram (EEG) contains valuable information obtained noninvasively that can be used for assessment of brain's processing capacity of patients with psychiatric disorders. The purpose of the present work was to evaluate possible differences in EEG complexity between deficit (DS) and nondeficit (NDS) subtypes of schizophrenia as a reflection of the cognitive processing capacities in these groups. A particular nonlinear metric known as Lempel-Ziv complexity (LZC) was used as a computational tool in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The data presented here are part of a larger study to probe the electrophysiological deviations associated with the DS syndrome. Evidence of decreased dimensionality in DS patients (signal complexity) was reported by Cerquera et al 21 and evidence for evoked potential deviations in the same group were also reported under a separate cover. 22 Schizophrenia patients were recruited from the outpatient clinics of Wayne State University, Department of Psychiatry and Behavioral Neurosciences.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The data presented here are part of a larger study to probe the electrophysiological deviations associated with the DS syndrome. Evidence of decreased dimensionality in DS patients (signal complexity) was reported by Cerquera et al 21 and evidence for evoked potential deviations in the same group were also reported under a separate cover. 22 Schizophrenia patients were recruited from the outpatient clinics of Wayne State University, Department of Psychiatry and Behavioral Neurosciences.…”
Section: Introductionmentioning
confidence: 62%
“…6. Fast Fourier transform on artifact-free epochs (total length of about 5-7 minutes) to obtain spectral power (absolute and relative) at different bands (delta[1][2][3][4], theta[4][5][6][7][8], alpha[8][9][10][11][12], beta1[12][13][14][15][16][17][18][19][20], beta2[20][21][22][23][24][25][26][27][28][29][30], and gamma).…”
mentioning
confidence: 99%
“…In the present study, we further found that FuzzyEn values in the frontal ROI (FZ and AF3) showed positive correlations with PANSSP and PANSSN. Higher FuzzyEn values and higher PANSSP or PANSSN scores indicated a more serious disease (Kay et al, 1987; Leucht et al, 2005; Cerquera et al, 2017). These findings indicated that the higher complexity of EEG signals was associated with the more serious clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies on the diagnosis of depression and schizophrenia [88][89][90][91][92][93][94][95][96][97], the nonlinear EEG analysis have been reported, but no nonlinear EEG analysis with accuracy has been reported for comorbid psychotic disorders and depression in patients with epilepsy. Psychiatric comorbidities are common in patients with epilepsy [3], and associations for psychosis with the age at onset, duration of epilepsy, and seizure frequency have been reported.…”
Section: Comorbid Psychiatric Disordersmentioning
confidence: 99%